ART PEDAGOGIKA ZAMONAVIY TA’LIM-TARBIYANING INTEGRATIV OMILI - Haydarov, X.H. (SCIENCE and SOCIETY, 2025)
This article describes the meaning and content of the art pedagogical approach in the educational process.